2017
DOI: 10.1515/jppr-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters of onion thrips, Thrips tabaci Lindeman on onion cultivars

Abstract: Biological parameters of the onion thrips, Thrips tabaci Lindeman were studied on the following onion (Allium cepa L.) cultivars: Nasik Red Plus N-53, Onion Dr-301 (Krishna), Onion White, and Nasik Red, at 25±1 o C and 65±5% RH. Signifi cant (p < 0.05) diff erences were found in the life stages and fertility life tables on diff erent cultivars except in the pupal stages. More information about the biological parameters of T. tabaci on onion cultivars can help in designing Integrated Pest Management programs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
1
0
2
Order By: Relevance
“…These results support the results of Gill, et al (2015) who stated that the dry and hot weather can lead to an increase in the populations of T. tabaci and the severity of thrips injury to onion and other crops. Also, the current results confirm that the nymph stage was more affected by the weather factors than adult stage as indicated by with Hendawy, et al, (2011) and Moraiet and Ansari, (2014). The findings of Hamdy and Salem, (1994) (relatively high temperature have been associated with increase in onion thrips population, while high relative humidity and rainfall reduce thrips population) are consistent to our results.…”
Section: Influence Of Abiotic Factors On Population Dynamics Of Onion Thrips T Tabaci In Onion Plantssupporting
confidence: 93%
“…These results support the results of Gill, et al (2015) who stated that the dry and hot weather can lead to an increase in the populations of T. tabaci and the severity of thrips injury to onion and other crops. Also, the current results confirm that the nymph stage was more affected by the weather factors than adult stage as indicated by with Hendawy, et al, (2011) and Moraiet and Ansari, (2014). The findings of Hamdy and Salem, (1994) (relatively high temperature have been associated with increase in onion thrips population, while high relative humidity and rainfall reduce thrips population) are consistent to our results.…”
Section: Influence Of Abiotic Factors On Population Dynamics Of Onion Thrips T Tabaci In Onion Plantssupporting
confidence: 93%
“…Our results indicate that among the tested temperature levels 23 C is the optimal temperature for the reproduction of T. tabaci lineages. Based on the observed fecundity, the optimum temperature for maximum egg laying was at 23 C. Murai (2000) has reported that the fecundity of the L2 lineage was 270 eggs at 23 C on honey and pollen, however, the fecundity started to decrease at 25 C and dropped drastically to 62 eggs per female at 30 C. Thus, food source also affects life table parameters of T. tabaci (Moraiet et al, 2017). van Rijn et al (van Rijn, Mollema, & Steenhuis-Broers, 1995) reported that females of T. tabaci produced 27.5 eggs on cucumber at 25 C. Hassanzadeh et al (2003) reported on onion plants at 27 C an average of 31.63 eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Os modelos, em geral, apresentaram relação positiva entre a incidência do inseto e a temperatura, para as temperaturas máxima e média. Isso está de acordo com dados de outros autores que ressaltaram a importância da temperatura no incremento populacional de tripes em cebola (GONÇALVES, 1997;JIMÉNEZ et al, 2002;MORAIET;ANSARI, 2014 (SMITH et al, 2016).…”
Section: Notas Deunclassified
“…A umidade relativa apresentou relação inversa com a incidência do inseto. Isso está de acordo com a afirmação de que o tempo seco é fator de incremento populacional do inseto, como ressaltado por outros autores (GONÇALVES, 1997;JIMÉNEZ et al, 2002;RUEDA et al, 2007;MORAIET;ANSARI, 2014 (DOMICIANO et al, 1993;GONÇALVES, 1998;WAIGANJO et al, 2008; GONÇALVES; VIEIRA NETO, 2011).…”
Section: Notas Deunclassified